THE EFFECT OF NURSING ROUND TRAINING ON PATIENT SATISFACTION IN NURSING SERVICES AT RS X JAKARTA - Yohana Wiratikusuma; Justina Purwarini Acihayati; Sudibyo Supardi (Jurnal Ilmiah Keperawatan, 2023)
Nursing rounds is a method used by nursing to explore and discuss in depth the problems of nursing on the patient, as well as to know the implementation of care standard that has been performed to improve service quality. This research aims to see the effect of nursing rounds method training on patient satisfaction with nursing service at RS X. We use pra-experiment design research, pre and post-tests without control, conducted from July 207 to January 2018 in RS X Jakarta. The research sample is 46 respondents. The intervention of nursing rounds training to the nurse, the evaluation used questionnaire to the patient. Data analysis used Chi-Square and Mann Whitney Tests. The research shows that patient satisfaction with the nursing service in RS X is very satisfied 32.6%, satisfied 67.4%, and dissatisfied 0%. The analysis of respondent characteristics (age, education, time of care, occupation, the person in charge of the medicine cost) and patient satisfaction (intangibility, responsiveness, reliability dimensions) have no relation. Nursing rounds significantly improve patient satisfaction with the nursing service in Empathy (35.4%) and Assurance (47.5%). The increase in patient satisfaction after the nursing round in Empathy (P=0.007) and Assurance (P=0.001) dimensions in male patients is higher than in female patients (P=0.035). From the research results above, tangibility, responsiveness, and reliability dimensions need to be improved by implementing nursing rounds in the ward. It shall be performed simultaneously to enhance the satisfaction of nursing service.